2021
DOI: 10.1186/s13075-021-02476-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of disease activity on impaired glucose metabolism in patients with rheumatoid arthritis

Abstract: Objective To explore glucose metabolism in rheumatoid arthritis (RA) and its association with insulin resistance (IR) risk factors and disease activity indicators, including matrix metalloproteinase-3 (MMP3). Methods This single-center study included 127 non-diabetic subjects: 90 RA patients and 37 matched controls. IR-related risk factors, disease activity (DAS28-ESR/CRP), concentrations of inflammation markers, MMP3, glucose, specific insulin, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…Our data confirm previous studies that show a higher level of insulin resistance among RA participants compared to controls [ 41 ]. Insulin resistance in RA is multifactorial, with corticosteroid treatment and systemic inflammation likely playing a major role [ 41 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data confirm previous studies that show a higher level of insulin resistance among RA participants compared to controls [ 41 ]. Insulin resistance in RA is multifactorial, with corticosteroid treatment and systemic inflammation likely playing a major role [ 41 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our data confirm previous studies that show a higher level of insulin resistance among RA participants compared to controls [ 41 ]. Insulin resistance in RA is multifactorial, with corticosteroid treatment and systemic inflammation likely playing a major role [ 41 ]. Skeletal muscle mitochondrial dysfunction has been implicated in insulin resistance [ 9 , 12 , 42 ], but this has not been previously reported in RA.…”
Section: Discussionsupporting
confidence: 92%
“…In SLE and RA patients, Cpeptide demonstrated a statistically significant positive connection with ESR and HOMA-B (P=0.004, P=0.000, and P=0.019, P=0.041, respectively). Additionally, according to Risti et al (34) , ESR was a standalone predictor of elevated C-peptide concentration (P= 0.133, P = 0.022). According to a recent study Martín-González et al (35) on RA patients, hyperglycemia brought on by insulin resistance causes beta-cell malfunction, which manifests as increased insulin and C-peptide production.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, compared to RA patients in remission, RA patients with active disease seem to have less stable and more vulnerable plaques which increases the probability of an acute CV event 40 . RA activity represents an independent risk factor for impaired glucose metabolism which is known to be an independent risk factor for cardiovascular diseases 41 . In contrast, Jonsson et al 42 , Roman et al 35 and Cuomo and colleagues 43 have shown in their researches that there is no correlation between IMT and disease activity, while Semb et colleagues stated that there is a positive correlation of CP vulnerability and RA disease activity assessed with CDAI but not with DAS28 40 .…”
Section: Discussionmentioning
confidence: 99%